Effects of Warming and N Deposition on the Physiological Performances of Leymus secalinus in Alpine Meadow of Qinghai-Tibetan Plateau - Shen, Hao; Dong, Shikui; Li, Shuai; Wang, Wenying; Xiao, Jiannan; Yang, Mingyue; Zhang, Jing; Gao, Xiaoxia; Xu, Yudan; Zhi, Yangliu; Liu, Shiliang; Dong, Quanming; et al. (Frontiers in Plant Science, 2020)
Warming and Nitrogen (N) deposition are key global changes which may affect eco-physiological process of territorial plants. In this paper, we examined the effects of warming, N deposition and their combination on the physiological performances of Leymus secalinus. Four treatments were established in an alpine meadow of Qinghai-Tibetan plateau: control (CK), warming (W), N deposition (N) and warming plus N deposition (NW). Warming significantly decreased the photosynthetic rate (Anet), stomatal conductance (gs), intercellular CO2 concentration (Ci) and transpiration rate (Tr), while N deposition and warming plus N deposition significantly increased those parameters of Leymus secalinus. Warming significantly increased the VPD and Ls, while N deposition and warming plus N deposition had a significant positive effect. Warming negatively reduced the leaf N content, Chla, Chlb, and total Chl content, while N deposition significantly promoted these traits. Warming, N deposition and their combination significantly increased the activity of SOD, POD and CAT. Besides, warming and warming plus N deposition significantly increased the MDA content, while N deposition significantly decreased the MDA content. N deposition and warming plus N deposition significantly increased the Rubisco activity while warming showed no significant effect on Rubisco activity. N deposition and warming plus N deposition significantly increased the Fv/Fm, ΦPSII, qP, and decreased NPQ, while warming significantly decreased the Fv/Fm, ΦPSII, qP, and increased NPQ. N deposition strengthened the relations between gs, Chl, Chla, Chlb, Rubisco activity and Anet. Under warming, only gs showed a significantly positive relation with Anet. Our findings suggested that warming could impair the photosynthetic potential of Leymus secalinus enhanced by N deposition. Additionally, the combination of warming and N deposition still tend to lead positive effects on Leymus secalinus in short term.